Neuropsychological Test Barcelona-2: Theoretical and Practical Aspects - Liutsko, L; Peña-Casanova, J; Rivera-Avila, N; Vinaixa-Campos, L; Cáceres-Guillén, I; Quiñones-Úbeda, S; Sánchez-Benavides, G (KnE Life Sciences, 2018)
The Barcelona test (TB) is an instrument of neuropsychological assessment, developed under the influence of Luria’s ideas, and published in 1990 [1]. It explores the main cognitive functions and allows the design of graphic profiles similar to those of the Boston Test for the diagnosis of aphasia. Objective: To present the theoretical and practical characteristics of a new version of the test, the Test Barcelona-2. The new and computerized versions of test structure is described here with six modules established: (1) Language-attention-orientation; (2) Reading and writing; (3) Motorpraxis; (4) Perception-gnosis; (5) Memory; (6) Abstraction-execution. As a novelty, test allows the selection for specific profiles: alpha, beta, abbreviated, aphasia, and ecological-forensic approach. The types of variables condition a different statistical approach and a differentiated form of graphic expression. The new test presents a modular structure, which allows determining intra- and inter-module dissociations. Computerization greatly facilitates the work of the clinician. In the case of aphasia the test allows to differentiate easily all its clinical forms. Keywords: Test Barceona-2, neuropsychological test; computerized workstation, modular structure